Developments in composite extrusion of complex profiles for automotive applications. (2019) - Schulze, A.; Dahnke, C.; Tekkaya, A.E.
Abstract: In recent years, the composite extrusion process has been developed to manufacture aluminum profiles with embedded high-strength steel reinforcements. Based on the fundamental understanding, the process is extended to manufacture reinforced profiles for automotive applications. The manufacturing of reinforced composite profiles under industrial conditions causes new challenges regarding the die design. In comparison to existing die designs for the academic environment, the new concept has to consider lower wall thicknesses and higher extrusion speeds. To overcome the mentioned challenges, FEM simulations are carried out to optimize the tool design and ensure a reliable economical production of the profiles